2016
DOI: 10.1002/jbm.b.33776
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and biocompatibility evaluation of bacterial cellulose‐based wound dressing hydrogel: effect of electron beam irradiation doses and concentration of acrylic acid

Abstract: The use of bacterial cellulose (BC)-based hydrogel has been gaining attention owing to its biocompatibility and biodegradability. This study was designed to investigate the effect of radiation doses and acrylic acid (AA) composition on in vitro and in vivo biocompatibility of BC/AA as wound dressing materials. Physical properties of the hydrogel, that is, thickness, adhesiveness, rate of water vapor transmission, and swelling were measured. Moreover, the effect of these parameters on skin irritation and sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 44 publications
2
28
0
Order By: Relevance
“…Bacterial cellulose is non-biodegradable in the human body because of the absence of cellulase enzyme 16 . Based on this, the previous abovementioned potential scaffold properties, and promising results of our previous studies 14 , 15 , BC/AA hydrogel may act both as a cell carrier and a wound dressing. Besides, the most severe forms of injury require exogenous cells for skin tissue regeneration.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Bacterial cellulose is non-biodegradable in the human body because of the absence of cellulase enzyme 16 . Based on this, the previous abovementioned potential scaffold properties, and promising results of our previous studies 14 , 15 , BC/AA hydrogel may act both as a cell carrier and a wound dressing. Besides, the most severe forms of injury require exogenous cells for skin tissue regeneration.…”
Section: Introductionsupporting
confidence: 58%
“…Furthermore, in vivo studies demonstrated that the wound healing rate was faster in the BC/AA hydrogel treatment group than that in the no treatment group (negative control) and Intrasite Conformable ® hydrogel treatment group (positive control) based on gross appearance and histological evaluation 14 . Additionally, the BC/AA hydrogel did not induce skin irritation on rabbits or skin sensitivity on guinea pigs 15 .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…ROS and RNS can change the membrane potential of mitochondria, leading to the release of Cyt-c [40]. The release of Cyt-c activates caspase-3 [41], which is the final effector caspase in the caspase cascade and is the common downstream effector of multiple apoptotic pathways [42]. Caspase-3 induces apoptosis and thereby drives the death of β-cells resulting in insufficient insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…To prepare suitable interfacial interactions, the surface properties should be improved appropriately . Physical treatments such as corona treatment, plasma treatments, and electron beam irradiation, chemical treatments like alkali treatment, silane treatment, and acetylation treatment, and so forth. and the surface modifications of the fibers have been performed to ameliorate the adaptability between polymer matrices and the surfaces of the natural fibers.…”
Section: Introductionmentioning
confidence: 99%